Mercury releasing from amalgam with disinfectan solution - Viona Diansari; Ellyza Herda (Faculty of Dentistry Universitas Padjadjaran, 2008)
Amalgam is widely used for posterior restoration because of its strength compare to the other restorative materials. However, the mercury released in amalgam still becomes a controversy and its harmfull effects to human. Researches show that the mercury released occurs when mercury ion is dissolved in acid or oxidizing solutions. In dentistry, a disinfectant that is used for sterilizing instruments, such as hand instrument and handpiece previously used during the replacement process of amalgam restoration can make mercury dissolving from amalgam residue in the instruments. The number of mercury ion dissolving in disinfectant solution depends on disinfectants pH, concentration, contact time, redox potential, and Sn content in amalgam matrix phase Ag-Hg. The process of mercury released from amalgam to disinfectant solutions is caused by the ability of disinfectant in oxidizing mercury metal (elemental) to become the dissolvable mercury ion. Therefore, dentists and clinicians should be carefully certain procedures of disinfectant waste disposal that contain mercury ion, in order to avoid toxic contamination of mercury ion that can be dangerous to the environment.